French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes